Effective Learning Strategies in Elementary Science Education - Syarifuddin, Syarifuddin; An Shoriah, Kamilah; Novelia, Liza; Herdianti, Noviani; Titin, Elyu Danti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Science learning in elementary schools is very important to foster scientific attitudes, critical thinking skills, and students' scientific knowledge base. However, unmotivated students, monotonous learning methods, and limited resources are some of the challenges still faced in the science learning process. Using a qualitative descriptive literature study, this research aims to explore effective science learning methods in primary schools. The results showed that question-based learning approaches, experiments, contextual approaches and cooperative learning can improve students' motivation, engagement and understanding of science concepts. In addition, the utilization of digital media, the active role of teachers as facilitators, diverse evaluations, and support from parents and the school environment are also important for the success of science learning. Therefore, an effective science learning strategy is needed.